Molecular Characterization of Citrobacter freundii Isolated from Neonates in Neonatal Intensive Care Unit of Nepal - Thapa, B; Tribuddharat, C (Journal of Nepal Paediatric Society, 2012)
Introduction: Nosocomial Citrobacter spp. is emerging as a successful nosocomial pathogen in neonates in Nepal. The important risk factor being poor infection prevention and control practices. The objective of this study was to investigate the clonal relatedness of Citrobacter freundii isolated from clinical and nonclinical sources in Neonatal Intensive Care Unit (NICU) and to determine the presence of Extended Spectrum Beta-Lactamase (ESBL) genes and class 1 integron element. Materials and Methods: Polymerase chain Reaction (PCR) and PCR-Randomly Amplified Polymorphic DNA typing of the isolates were performed in three isolates to amplify class 1 integron element integrase gene, ESBL genes, and to study the clonal relatedness, respectively. Results: Two isolates harbored class 1 integron element. The blaCTX-M was present in all isolates and blaTEM-1 was present in one isolate. An isolate carried blaCTX-M and blaTEM-1 genes. All of these isolates were not clonally related. Conclusion: The study for the first time documented the emergence and spread of ESBL genes and class 1 integron element in multidrug resistant C. freundii in Nepal and urge for monitoring and surveillance of these strains. J. Nepal Paediatr. Soc. 32(2) 2012 132-135 doi: http://dx.doi.org/10.3126/jnps.v32i2.5804